Association between sleep duration and hearing threshold shifts of adults in the United States: National Health and Nutrition Examination Survey, 2015-2016 - Lili Long; Yuedi Tang (BMC, 2023)
Abstract Background Obstructive sleep apnea (OSA) is linked to hearing loss (HL). Another sleep characteristics, sleep duration might also be associated with HL, but prior evidence is limited. This study is aimed to investigate the association between sleep duration and hearing level in the adult US population. Methods In total, a sample of 2777 individuals aged 20-69 years from the 2015-2016 National Health and Nutrition Examination Survey cycle (NHANES, 2015-2016) were investigated in this study. Self-reported sleep duration data was classified into the short-sleep (< 7 h), normal-sleep (7-9 h), and long-sleep (> 9 h) group. Multivariable linear regression models between sleep duration and hearing threshold shifts were estimated. Interactions between sleep duration and age, gender, race, OSA were also considered, and the study population was stratified by age, gender, race, and OSA to analyze the potential disparities among adults in different subgroups. Results Long-sleep duration was positively associated with speech- and high-frequency pure-tone average (PTA) thresholds with statistical significance (β = 1.31, 95%CI: 0.10, 2.53, P = 0.0347, and β = 2.71, 95%CI: 0.69, 4.74, P = 0.0087, respectively). When stratified by age, short sleep duration was positively associated with low-, and speech-frequency PTAs (P = 0.0140 and 0.0225, respectively) for adults aged 40-59 years, and long-sleep duration was positively associated with low-, and speech-frequency PTAs (P = 0.0495 and 0.0142, respectively) for adults aged 60-69 years with statistical significance. There was statistically significant interaction between OSA and sleep duration on speech-frequency PTA, but no significant interaction between either gender or race with sleep duration on hearing thresholds among US adults. Conclusion Short/long sleep durations are associated with worse hearing level comparing to sleep 7-9 h in the American adults. Nonoptimal sleep duration may be a potential risk factor for HL.